Phased array ultrasonic S-scan testing of near-detection-surface defects based on a background subtraction algorithm. (1st March 2022) - Tian, Yukuo; Xu, Guocheng; Wei, Lingbo; Zhou, Guanghao; Lin, Yuting; Fan, Qiuyue; Gu, Xiaopeng
Abstract: In phased array ultrasonic sector scanning testing, echoes from defects near the detection surface are often overlapped with interface echoes and cannot be characterized. Based on linear acoustic theory, a mathematical model combining the background subtraction and the sum of squares differences algorithm is established to extract the characteristics of near-detection-surface defect echoes. The upper surface of the artificial notch defect is used as a near-detection-surface defect for detection. Specially, linear interpolation algorithm is used to suppress the effect of residual interface echo on the defect echo feature extraction and the effect of different interpolation factors is analyzed. The defect location and size were calculated based on the extracted defect characteristics. The simulation and experimental results indicate that the model can effectively extract the near-detection-surface defect echoes characteristics. Furthermore, when the interpolated signal reaches at least 500 MHz, residual interface echoes can be effectively suppressed. More importantly, according to the extracted defect echo characteristics, the localization and quantitative accuracies of near-surface defects can reach 0.2 mm and 0.3 mm, respectively. These findings provide an effective strategy for phased array ultrasonic sector scanning testing of near-detection-surface defects.